Industrial waste management using the rapid impact assessment matrix method for an industrial park - A.A. Shayesteh; O. Koohshekan; F. Khadivpour; M. Kian; R. Ghasemzadeh; M. Pazoki (Global Journal of Environmental Science and Management)
Due to the growth of population and industrialization, a great number of problems associated with producing industrial wastes have been created for both the environment and human beings. The industrial waste management in Brujen industrial park, located in the western part of Iran, has been investigated in this study using the environmental rapid impact assessment matrix technique. For this purpose, the effective activities and components were classified. The determination of the best scenarios with the least impact on the environment was performed by developing the scenarios for possible industrial waste disposal and making calculations by the rapid impact assessment matrix method. The components of the environment were first classified into physical/chemical, economic/operational, biological/ecological, and social/cultural items. Afterward, with respect to the criteria of the rapid impact assessment matrix method, the importance of environmental impacts was determined by standard scoring of the developed scenarios. Ultimately, the environmental score of each component for the scenarios was calculated using the rapid impact assessment matrix method, and the best scenario with the least environmental impacts was selected through a quantitative comparison. According to the results, scenario 3 (pyrolysis) and scenario 1 (recycling) were found to have the most negative impact and the most positive impact on the environment. Scenario 4 (incineration), with its severe air pollution, obtained a high negative score and was excluded from the options. As a result, two systems of recycling (scenario 1) and the sanitary landfill (scenario 2) were identified as complementary to each other and were selected as a solid waste management method.